Selenium WebDriver with Java : basic to advanced+ interview guide - Shetty, Rahul (Packt Publishing, 2018)
"This course covers core Java Basics + Selenium Webdriver + Advanced Selenium + Interview Preparation +Framework design (TestNG, ANT, Pageobject, Maven, Jenkins, Excel Datadriven, Cucumber, log4j) + Selenium Grid + Database Testing + Performance Testing on Selenium scripts + Mobile testing Basics. All the topics were taught from basic to advanced level with a lot of tricks and tips which makes users to get perfection on the things. On course completion, you will be mastered in Selenium Automation Testing and can implement successfully it in your workplace. We assume that students have no experience in automation/coding and start every topic from scratch and basics. At the end of this course, you can pick any web application over the internet and can automate it whatever the way you want."--Resource description page